The effects of a music intervention during port catheter placement on anxiety and stress - Nora K. Schaal (Nature Portfolio, 2021)
Abstract Studies have shown that perioperative music interventions can reduce patients’ anxiety levels. However, in small operations like port catheter surgery evidence is sparse. The present single-blinded, randomised controlled two-armed study included 84 female patients undergoing port catheter placement who were randomly assigned to either listening to music during surgery vs. no music intervention. The medical staff was blind to group allocation. On the day of the surgery anxiety and stress levels were evaluated using subjective (STAI questionnaire, visual analogue scales) and objective (vital parameters, salivary cortisol) parameters at different time points (before the surgery, at the end of the surgery and 1 h post-surgery). The music group showed significant reductions of systolic blood pressure (from 136.5 mmHg ± 26.1 to 123.3 mmHg ± 22.0, p = .002) and heart rate (from 75.6 bpm ± 12.3 to 73.1 bpm ± 12.2, p = .035) from beginning of the surgery to skin suture, whereas the control group did not. No significant effects of the music intervention on subjective anxiety measures or salivary cortisol were revealed. In sum, the study demonstrates that a music intervention during port catheter placement positively influences physiological anxiety levels, whereas no effects were revealed for subjective anxiety and salivary cortisol. Thus, music can be considered as a low cost addition in clinical routine in order to reduce patients’ heart rate and blood pressure. Future studies are encouraged to further explore the differential effects of intraoperative music interventions on physiological, endocrinological and subjective anxiety levels.